Pertunjukan Silat Muncak Di Perguruan Pendekar Bungsu Desa Kampung Bunga Kecamatan Rakit Kulim Kabupaten Indragiri Hulu Provinsi Riau - Fitriani Fitriani; Yahyar Erawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study aims to determine the Muncak Silat Performance of the Pendekar Bungsu School in Rakit Kulim District, Indragiri Hulu Regency, Riau Province. The method used is a qualitative method with descriptive analysis. Data collection was carried out using observation, interview and documentation techniques. The research subjects were 4 people, namely the Pendekar Bungsu silat teacher, Tuo Laman, Musicians, and the Audience. Qualitative data analysis was carried out interactively and continuously until complete, namely data reduction, data display, conclusion drawing/verification. Based on the results of the study on the Muncak Silat Performance at the Pendekar Bungsu School in Kampung Bunga Village, it was concluded that the Muncak silat performance usually consists of 2 to 4 martial artists in the arena or in a large yard, each martial artist uses a sword as a tool to demonstrate all movements harmoniously. In the Muncak silat performance, the martial artists wear clothing consisting of a peci, Malay clothes equipped with a sampin cloth. Each movement of the silat is accompanied by music played by 3 musicians using gongs or tetawak, calempong and silat drums. Silat movements and music go hand in hand in harmony, so that it becomes a performance that can be performed by a large audience.